2011
DOI: 10.1364/boe.2.002339
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz reflectometry of burn wounds in a rat model

Abstract: We present sub-millimeter wave reflectometry of an experimental rat skin burn model obtained by the Terahertz Time-Domain Spectroscopy (THz-TDS) technique. Full thickness burns, as confirmed by histology, were created on rats (n = 4) euthanized immediately prior to the experiments. Statistical analysis shows that the burned tissue exhibits higher reflectivity compared to normal skin over a frequency range between 0.5 and 0.7 THz (p < 0.05), likely due to post-burn formation of interstitial edema. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 25 publications
3
46
0
1
Order By: Relevance
“…[31][32][33] We have previously shown that the double Debye model, proposed by Pickwell et al, 19 can be extended to explain the higher terahertz reflectivity of moderate burn samples immediately postinjury. 30 In accordance with the general burn literature, 2 an increase in the water content of the burned tissue, due to formation of interstitial edema, has been experimentally observed using THz spectroscopy. [30][31][32][33] Furthermore, we proposed that the sensitivity of THz waves to the postburn reduction in the number and size of discrete normal skin structures, such as microvasculature, sweat glands, and hair follicles can be used as a source of signal contrast in THz burn imaging.…”
Section: Terahertz Modality For Characterization Of Burn Woundssupporting
confidence: 70%
See 2 more Smart Citations
“…[31][32][33] We have previously shown that the double Debye model, proposed by Pickwell et al, 19 can be extended to explain the higher terahertz reflectivity of moderate burn samples immediately postinjury. 30 In accordance with the general burn literature, 2 an increase in the water content of the burned tissue, due to formation of interstitial edema, has been experimentally observed using THz spectroscopy. [30][31][32][33] Furthermore, we proposed that the sensitivity of THz waves to the postburn reduction in the number and size of discrete normal skin structures, such as microvasculature, sweat glands, and hair follicles can be used as a source of signal contrast in THz burn imaging.…”
Section: Terahertz Modality For Characterization Of Burn Woundssupporting
confidence: 70%
“…30 In accordance with the general burn literature, 2 an increase in the water content of the burned tissue, due to formation of interstitial edema, has been experimentally observed using THz spectroscopy. [30][31][32][33] Furthermore, we proposed that the sensitivity of THz waves to the postburn reduction in the number and size of discrete normal skin structures, such as microvasculature, sweat glands, and hair follicles can be used as a source of signal contrast in THz burn imaging. 30,33 In this paper, we formulate a hypothesis for a burn diagnosis criterion based on in vivo terahertz reflection spectroscopy results obtained from second-and third-degree burns over a 72-hour period after injury.…”
Section: Terahertz Modality For Characterization Of Burn Woundssupporting
confidence: 70%
See 1 more Smart Citation
“…Recently, feasibility studies using terahertz (THz) imaging have been carried out with the objective of gauging its potential as a burn severity assessment tool [12]. Reflective THz imaging relies on the dielectric properties of water to reflect the signal of interrogated tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Yanık hasarının diagnozu için araştırmacılar tarafından hem ex-vivo hem de in vivo deneysel çalışmalar yapılmaktadır. [59][60][61] Bir çalışmada, eksize doku ör-neklerinin yanmış doku kesitinden suyun uzaklaş-tırılması ile normal deriye kıyasla daha düşük terahertz yansıması oluştuğu bildirilmiştir. 59 Bir diğer çalışmada ise derin dermal ile tam katman yanıklarını ayırt etmek için terahertz spektroskopinin deneysel olarak güvenli olduğu bildirilmiştir.…”
Section: Terahertz Spektroskopi̇unclassified